Water-related ecosystems' mapping and assessment based on remote sensing techniques and geospatial analysis: The SWOS national service case of the Greek Ramsar sites and their catchments - M. Tompoulidou; Chatziiordanou, E.; Apostolakis, A.; R. Hofer; K. Weise; C. Ververis; Fitoka, E. (2020)
Water-related ecosystems' mapping and assessment based on remote sensing techniques and geospatial analysis: The SWOS national service case of the Greek Ramsar sites and their catchments. Remote Sensing of Environment 245 (2020) 111795. doi.org/10.1016/j.rse.2020.111795